A Career Guidance and Career Planning Assessment Method Based on Improved Correlation Analysis. (2nd June 2022) - Han, Yun
Abstract : The number of college graduates in China has dramatically risen in recent years, the employment structural contradiction is evident, and the pressure on employment is gradually increasing. How to improve the employment rate of graduates and the quality of employment is an important issue at present. In order to fundamentally solve the employment problem, there are some other ways besides changing the talent cultivation mode of colleges and universities, such as carrying out career guidance work. At present, the career guidance model in China's universities is still limited to the traditionalized guidance model, which is too consistent. In order to meet the needs of the development of the market economy and the development of students' individuality, it is necessary to study the construction of a personalized career guidance model. This study first analyzes the current situation of career guidance work in China's colleges and universities and puts forward the importance and necessity of building a personalized career guidance model. Subsequently, based on improved correlation analysis, this research provides a method for evaluating employee knowledge and career planning. The experimental results suggest that the proposed method can accurately assess the impact of job counseling and establish the groundwork for future job counseling and career planning work in colleges and universities.